Amino acid supplementation of wheat and milo for the finishing pig - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
Two experiments involving 214 pigs were conducted to evaluate milo and wheat as the sole sources of amino acids for finishing swine, and the effects of supplementing these grains with lysine and methionine. Without supplemental lysine wheat and milo diets were inadequate for finishing pigs as measured by growth rate, feed efficiency, and loin eye area. There were no significant differences in daily gain or feed efficiency among the pigs fed wheat + lysine, milo + lysine + methionine, wheat + soybean meal or milo + soybean meal. Pigs fed milo supplemented with only lysine gained slower, had a smaller loin eye area, and tended to be less efficient in feed utilization than the pigs fed milo + soybean meal. The results indicate that lysine is the only limiting amino acid in wheat for the finishing pig, while milo must be supplemented with both lysine and methionine.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Amino acid; Wheat; Milo; Finishing pig; Methionine